Remote Sensing and GIS-Based Assessment of Karst Development in Libya: Evidence from the Al-Jabal Al-Akhdar–Benghazi Plain and Tripolitanian Pre-desert (Al-Farooq Journal of Sciences, 2026)
Karst aquifers are unique hydrogeological environments that are characterized by their complex surface and groundwater drainage systems such as dolines, sinkholes, caves, springs, and karst lakes. The present paper aims to investigate the distribution pattern of karst features and analyze their associations with other geomorphological lineaments in two large karst areas of Libya, namely, Al-Jabal Al-Akhdar–Benghazi Plain, which is located in northeastern Libya, and Tripolitanian Pre-desert, which is located in northwestern Libya. The study used Sentinel-2 multispectral satellite imagery, normalized difference water index (NDWI), 12.5-m ALOS PALSAR digital elevation models (DEMs), and Geographic Information System to delineate karst landforms and analyze their relationships with lineament density. The study revealed several karst landforms, including dolines, sinkholes, closed depressions, caves, springs, and karst lakes. These karst landforms were delineated and extracted from the input data by using different thresholds. In addition, lineaments were extracted from the input imagery and analyzed for their density and water-related anomalies. Subsequently, thematic karst density maps were generated and compared to identify karst variability. The study showed that Al-Jabal Al-Akhdar–Benghazi Plain has a more developed karst system, as demonstrated by the presence of well-developed doline fields, larger and deeper closed depressions, higher number of springs and karst lakes, and higher density of large-scale karst features. On the other hand, the Tripolitanian Pre-desert is generally more arid and contains a lower number of closed depressions, dolines, and caves. The study’s results also indicate that dolines are distributed according to the pattern of lineaments, suggesting that these features were formed as a result of carbonate rock dissolution through infiltration groundwater flow and enhanced by structural discontinuities. In addition, karst density analysis revealed local areas with high concentrations of karst features that may be prospective for groundwater exploration and sinkhole hazard assessment. Finally, the creation of an integrated preliminary karst-susceptibility map revealed that the areas in northern Libya, particularly in Al-Jabal Al-Akhdar–Benghazi Plain and Tripolitanian Pre-desert, have higher levels of karst susceptibility due to the presence of carbonate rocks, lineaments, associated groundwater features, and karst landforms. Overall, the present study demonstrated that the analysis of satellite imagery, combined with 12.5-m ALOS PALSAR DEDMs, NDWI, and GIS analysis can be useful in delineating karst-susceptible areas and assessing groundwater potential and sinkhole hazards in Libya.
Keywords: Remote Sensing, GIS, Karst Landforms, Al-Jabal Al-Akhdar–Benghazi Plain, Tripolitanian Pre-desert, Libya